DAKWAH MELALUI ORGANISASI NAHDLATUL 'ULAMA - Muhammad Munif (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2013)
Nahdlatul 'Ulama (the Renaissance of Ulama) is one of the big Islamic organisations in Indonesia, which has shown its ability to guide Muslim community to get out from difficult situation in national life. However, it needs strong framework of thought which comes from living tradition in the members of NU. As an religious organisation, NU determined political goals that are based on the doctrine of Ahlus Sunnah wa/ Jama'ah, decreed in basis for the NU organization platform in In its efforts in spreading da'wah, NU has many activities that are related to Islamic da'wah, which include educational institution, pesantren, mosque and politics. This is a for of an organized da'wah.